2018
DOI: 10.1016/j.livres.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic lipid homeostasis by peroxisome proliferator-activated receptor gamma 2

Abstract: Peroxisome proliferator-activated receptor gamma (PPARγ or PPARG) is a ligand-activated transcription factor belonging to the nuclear hormone receptor superfamily. It plays a master role in the differentiation and proliferation of adipose tissues. It has two major isoforms, PPARγ1 and PPARγ2, encoded from a single gene using two separate promoters and alternative splicing. Among them, PPARγ2 is most abundantly expressed in adipocytes and plays major adipogenic and lipogenic roles in the tissue. Furthermore, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 106 publications
4
85
0
Order By: Relevance
“…Based on Table 7 and Table 8 showed that the change in PPARγ2 gene expression in liver tissue was higher than adipose tissue. Normally, PPARγ2 is most abundantly expressed in adipocytes and plays major adipogenic and lipogenic roles in the tissue (Lee et al, 2018). Because the rats in the present study received high fat and high fructose diet, it was possible to cause fatty liver.…”
Section: Treatmentsmentioning
confidence: 91%
See 2 more Smart Citations
“…Based on Table 7 and Table 8 showed that the change in PPARγ2 gene expression in liver tissue was higher than adipose tissue. Normally, PPARγ2 is most abundantly expressed in adipocytes and plays major adipogenic and lipogenic roles in the tissue (Lee et al, 2018). Because the rats in the present study received high fat and high fructose diet, it was possible to cause fatty liver.…”
Section: Treatmentsmentioning
confidence: 91%
“…Because the rats in the present study received high fat and high fructose diet, it was possible to cause fatty liver. According to Souza-Mello (2015), in non-alcoholic fatty liver disease (NAFLD) showed a high abnormality of PPARγ expression in the liver (Lee et al, 2018).…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many genes involved in adipogenic programs play a key role in the initiation and progression of NAFLD [7]. Peroxisome proliferation-activated receptor gamma 2 (PPARγ), a master regulator of adipogenesis [14], is frequently upregulated in NAFLD [15]. Similarly, sterol regulatory binding element protein-1c, SREBP-1c (protein coded by the gene SREBF1), a major driver of hepatic DNL, is upregulated in NAFLD [7].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, sterol regulatory binding element protein-1c, SREBP-1c (protein coded by the gene SREBF1), a major driver of hepatic DNL, is upregulated in NAFLD [7]. Consequently, many coregulators and downstream target genes of PPARγ and SREBP-1c are also perturbed in the context of NAFLD [15]. Another intriguing observation about NAFLD patients is their lower levels of hallmark liver tissue maintenance genes of the liver such as Hepatocyte Nuclear Factor 4α (HNF4α) and…”
Section: Introductionmentioning
confidence: 99%